2021
DOI: 10.1002/joc.7321
|View full text |Cite
|
Sign up to set email alerts
|

Observed changes in seasonal drought characteristics and their possible potential drivers over Pakistan

Abstract: Long‐term drought monitoring and its assessment are of great importance for meteorological disaster risk management. The recurrent spells of heat waves and droughts have severely affected the environmental conditions worldwide, including Pakistan. The present work sought to investigate the spatiotemporal changes in drought characteristics over Pakistan during Rabi and Kharif cropping seasons. The role of large‐scale circulation and interannual mode of climate variability is further explored to identify the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 72 publications
(134 reference statements)
1
33
0
Order By: Relevance
“…In some areas, the severity and frequency of droughts can lead to water scarcity conditions, whereas overexploitation of existing water resources can worsen the effects of droughts [85]. Various studies demonstrate that drought is among the most dangerous distractive disaster in the current warming world [86][87][88][89], impacting natural resources such as sustainable water and environment, agriculture, ecology, and biodiversity [79,[90][91][92]. The present study shows that drought occurrences are increasing, which may lead to severe impacts on water resources and agriculture management in a country with a high population density like Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…In some areas, the severity and frequency of droughts can lead to water scarcity conditions, whereas overexploitation of existing water resources can worsen the effects of droughts [85]. Various studies demonstrate that drought is among the most dangerous distractive disaster in the current warming world [86][87][88][89], impacting natural resources such as sustainable water and environment, agriculture, ecology, and biodiversity [79,[90][91][92]. The present study shows that drought occurrences are increasing, which may lead to severe impacts on water resources and agriculture management in a country with a high population density like Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…The daily precipitation and temperature datasets were summed to create the monthly and annual datasets. The standardized normalized homogeneity test (SNHT) was used to find the peaks and outliers in the data [49]. During data quality evaluation, it was found that only 2-3% of the data were missing which would not have a substantial impact on the results [49]; however, we still replaced the missing data with the average values of the nearby meteorological stations to maintain the quality [48].…”
Section: Methodsmentioning
confidence: 99%
“…The standardized normalized homogeneity test (SNHT) was used to find the peaks and outliers in the data [49]. During data quality evaluation, it was found that only 2-3% of the data were missing which would not have a substantial impact on the results [49]; however, we still replaced the missing data with the average values of the nearby meteorological stations to maintain the quality [48]. Next, we calculated the descriptive statistics in XLSAT Adin of Excel software, the details of which are presented in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…The use of such indices is regarded as an ingenious standardized approach based on precipitation scarcity [68]. The SPI is the most important and frequently used index for drought monitoring [15,[70][71][72][73]. This index computes a gamma probability distribution function for a precipitation time series.…”
Section: Standardized Precipitation Index (Spi)mentioning
confidence: 99%